2012
DOI: 10.4028/www.scientific.net/amr.490-495.213
|View full text |Cite
|
Sign up to set email alerts
|

Design of Electromagnetic Heating Control System with Rotational Scanning in Plastic Machinery

Abstract: The article analyzed the existing problems and deficiencies in the electromagnetic induction heating method in the production process of the current plastics machinery. Furthermore a solution is proposed to adopt rotational scanning heating via improving the power of the current heating controllers. Meanwhile, a systematic engineering approach is put forward, which is proved to be stable and reliable through industrial field trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Several electromagnetic induction researches have been reported recently. Zhu and Luo estimated the bending of thick plate by induction heating method 10 . Huseyin Karasu and Ibrahim Dincer 11 assessed the efficiency of wind energy transfer to heat by using induction heating method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several electromagnetic induction researches have been reported recently. Zhu and Luo estimated the bending of thick plate by induction heating method 10 . Huseyin Karasu and Ibrahim Dincer 11 assessed the efficiency of wind energy transfer to heat by using induction heating method.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and Luo estimated the bending of thick plate by induction heating method. 10 Huseyin Karasu and Ibrahim Dincer 11 assessed the efficiency of wind energy transfer to heat by using induction heating method. Furthermore, Huang and Cui 12 found that the electromagnetic induction heating could reduce the casting time and increase the production efficiency.…”
Section: Introductionmentioning
confidence: 99%